A novel topical combination of minoxidil and spironolactone for androgenetic alopecia: Clinical, histopathological, and physicochemical study. Issue 1 (25th December 2020) - Abdel‐Raouf, Hamza; Aly, Usama F.; Medhat, Walid; Ahmed, Shimaa S.; Abdel‐Aziz, Rasha T. A.
Abstract: Topical minoxidil 5% are effective in androgenetic alopecia (AGA). Spironolactone acts as an androgen antagonist by competitively blocking androgen receptors. Studying the effect of topical minoxidil 5% gel and spironolactone gel 1% in management of AGA. The study includes 60 patients diagnosed as AGA; (group I): treated with topical minoxidil gel 5%, (group II): with topical spironolactone gel 1% and group (III) treated with combined minoxidil 5% and spironolactone 1% gel. All patients were followed up monthly throughout the treatment period. Scalp biopsy was taken before and after 12 months. In group I, the clinical response was in 90% of patients with variable degrees in improvement, in group II, the clinical response was in 80% of patients, meanwhile, in group III the clinical response was in all patients (100%). Histopathological examination of skin biopsy after treatment revealed significant increase in anagen hair on the other hand, both telogen and vellus hair was significantly decreased meanwhile, the T/V ratio was significantly increased. The results of this work revealed that topical minoxidil gel 5% and topical spironolactone gel 1% were effective in treatment of AGA, while the combination of two agents was better in treatment.